Analisis dan Perbandingan Media Interaktif Kahoot dan Quizizz dalam Kemudahan Pembelajaran - Aditya Ahmad Fauzi; Fithriawan Nugroho; Wahyu Putra; Yossa Agung Pratama; Andria Rezki; Tri Dewi Yuni Utami (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2025)
Technological advancements have significantly impacted education, including more interactive learning methods. Kahoot and Quizizz are two platforms that utilize gamification to enhance student engagement in learning. This study aims to analyze and compare these interactive media in terms of ease of use, student engagement, and effectiveness in providing feedback. Using a qualitative method and a case study approach, data was collected through interviews and observations of teachers and students utilizing both platforms. The study's findings indicate that Kahoot is more effective in boosting student motivation through a competitive system, whereas Quizizz excels in independent learning flexibility and providing more detailed result reports. Therefore, the utilization of these platforms should be adjusted according to the learning objectives to be achieved..